2017
DOI: 10.1097/01.nep.0000000000000163
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention to Improve Cultural Competence in Graduate Nursing Education

Abstract: Noting the small number of studies on the influence of an entire curriculum on graduate nursing students' cultural competence, the researchers examined the effect of a curricular intervention using a pretest-posttest design. The study, conducted from 2012 to 2014, focused solely on the Doctor of Nursing Practice program at a midwestern university. Results from a pre- and postintervention faculty curriculum survey indicated that the percentage of courses including a cultural competence objective increased from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…Consideration of different learning styles of diverse student groups and determination of effective evidence-based teaching and learning interventions play an important role in helping students attain their educational goals. A current review of the literature revealed nurse educators implemented a variety teaching and learning strategies to enhance ADN, BSN, masters, and doctoral nursing students'cultural competence, such as: local or international service-learning projects (Adams, 2012;Amerson, 2010Amerson, , 2012Amerson & Livingston, 2014;Rogers-Walker, 2014;Schmidt, 2012), international immersion experiences (Czanderna, 2013), domestic immersion experiences (Larsen & Reif, 2011;Schroeder, 2012), global web-conferencing (Spalla, 2012), integration of cultural competence objectives in the curriculum (Creech et al, 2017;Jeffreys & Dogan, 2012;Jeffreys & Smodlaka, 1996;1998;1999a;1999b;Singleton, 2017), case studies, gaming, role play, face-to-face classrooms, and hybrid and online courses (Adams & Nevel, 2016a;Curtis, Bultas, & Green, 2011Halter et al, 2014), Cultural Discovery (Jeffreys & O'Donnell, 1997;Jeffreys & Dogan, 2012;Jeffreys, O'Donnell, & Xiao, 2010, 2016a, innovative field trip experience (Jeffreys, Bertone, Douglas, Li, & Newman, 2016a), flipped cultural simulation (McArthur, Mixer, & Fancher, 2016a), the use of low-and high-fidelity patient simulation (Garrido et al, 2014;Grossman et al, 2012;Halter et al, 2014;Odreman, 2016;Phillips et al, 2012;Rutledge et al, 2008), virtual simulation experience (VSE)…”
Section: Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consideration of different learning styles of diverse student groups and determination of effective evidence-based teaching and learning interventions play an important role in helping students attain their educational goals. A current review of the literature revealed nurse educators implemented a variety teaching and learning strategies to enhance ADN, BSN, masters, and doctoral nursing students'cultural competence, such as: local or international service-learning projects (Adams, 2012;Amerson, 2010Amerson, , 2012Amerson & Livingston, 2014;Rogers-Walker, 2014;Schmidt, 2012), international immersion experiences (Czanderna, 2013), domestic immersion experiences (Larsen & Reif, 2011;Schroeder, 2012), global web-conferencing (Spalla, 2012), integration of cultural competence objectives in the curriculum (Creech et al, 2017;Jeffreys & Dogan, 2012;Jeffreys & Smodlaka, 1996;1998;1999a;1999b;Singleton, 2017), case studies, gaming, role play, face-to-face classrooms, and hybrid and online courses (Adams & Nevel, 2016a;Curtis, Bultas, & Green, 2011Halter et al, 2014), Cultural Discovery (Jeffreys & O'Donnell, 1997;Jeffreys & Dogan, 2012;Jeffreys, O'Donnell, & Xiao, 2010, 2016a, innovative field trip experience (Jeffreys, Bertone, Douglas, Li, & Newman, 2016a), flipped cultural simulation (McArthur, Mixer, & Fancher, 2016a), the use of low-and high-fidelity patient simulation (Garrido et al, 2014;Grossman et al, 2012;Halter et al, 2014;Odreman, 2016;Phillips et al, 2012;Rutledge et al, 2008), virtual simulation experience (VSE)…”
Section: Strategiesmentioning
confidence: 99%
“…reported the most change occurring on the Cognitive subscale, the literature review revealed a few studies reporting the greatest change in SEST scores occurring in the Practical subscale (Adams, 2012;Creech et al, 2017;Singleton, 2017).…”
Section: Summary Of the Studymentioning
confidence: 99%
“…Aims and goals of cultural sensitivity in nursing education should be determined in order to increase cultural sensitivity of students (Creech et al, 2017). In line with these aims and goals, nursing educators should train qualified students so that the students may cope with the difficulties in the process of culturally sensitive healthcare service delivery (Chan & Sy, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The main approach to enhance cultural sensitivity is the integration of the subject to nursing curriculum. Other methods include individual lectures, experiencing different cultures and simulation practices about different cultures (Creech et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Educators must prepare culturally aware nurses for advanced practice and educator roles as a strategy to improve the quality of health education and health care outcomes of increasingly diverse populations across settings (American Association of Colleges of Nursing [AACN], 2017; National League for Nursing [NLN], 2016[NLN], , 2017. To reach this objective, nurse educators use a variety of teaching approaches to provide meaningful learning experiences for students to promote cultural awareness, sensitivity, and behavior skills in the classroom, simulation, online, and short-term immersion experiences (AACN, 2017;Creech et al, 2017;Levey, 2016Levey, , 2017aLonneman, 2015;NLN, 2016NLN, , 2017NLN, , 2018. However, graduate cultural diversity courses requiring an immersion experience can impose hardships for students based on finances, family, and work schedules (Levey, 2016(Levey, , 2017a(Levey, , 2017b(Levey, , 2017cLong, 2012;Sagar, 2014).…”
mentioning
confidence: 99%